Potential Sampling Errors in Stability Studies Due to Dead Volume in Closed System Transfer Devices. - Closset, Mélanie; Colsoul, Maire-Lise; Bihin, Benoît; Hecq, Jean-Daniel; Odou, Pascal; Galanti, Laurence (Journal of Pharmacy Technology, 2024)
Background: Closed system transfer devices (CSTD) help to reduce the exposure of healthcare professionals to hazardous drugs. They may be used in stability studies conducted on anticancer drugs. During a stability study about polyolefin bags of gemcitabine, Tevadaptor® device was suspected of causing a bias in the evaluation of the concentrations of the first aliquots extracted from the bags. Objective: The objectives are to determine whether the use of a CSTD to prepare a drug solution and to withdraw it from a bag can interfere on the measured concentration compared to the expected one and to suggest hypothesis to explain the phenomenon. Method: In the first experiment, three polyolefin bags of gemcitabine (5.4 mg/mL) were prepared under aseptic conditions using the Tevadaptor Luer Lock Adaptor®. The day of preparation, five aliquots of 3.8 ml each were sequentially withdrawn from each polyolefin bag using the same device. After one day, a new aliquot was withdrawn from each bag. In the second experiment, three polyolefin bags of gemcitabine (5.4 mg/ml) were prepared under aseptic conditions using a needle. One aliquot was extracted using a needle after the preparation from each bag, and another aliquot was extracted after one day. The concentrations of all aliquots were measured by liquid chromatography coupled to a photodiode array detector during the same run. Results and discussion: The concentrations of the first aliquots extracted on day zero from the polyolefin bags using the Tevadaptor Luer Lock Adaptor® exhibit an overestimation of 26% ([95%CI: 23%-29%] P<0.001) compared to the others. Overestimation is not found for subsequent aliquots, or while using a needle to bypass the Tevadaptor® device. Conclusion: This case highlights the bias that may arise when using CSTDs in stability studies. They should be used with comprehensive understanding of their technical specifications.